2009
DOI: 10.1101/lm.1445609
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory shapes the primary olfactory center of an insect brain

Abstract: The storage of stable memories is generally considered to rely on changes in the functional properties and/or the synaptic connectivity of neural networks. However, these changes are not easily tractable given the complexity of the learning procedures and brain circuits studied. Such a search can be narrowed down by studying memories of specific stimuli in a given sensory modality and by working on networks with a modular and relatively simple organization. We have therefore focused on associative memories of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 45 publications
2
96
2
Order By: Relevance
“…Indeed, plasticity of PN responses was observed both in Drosophila (Yu et al, 2004) and Apis (Fernandez et al, 2009). Supporting this view, LTM formation induces structural reorganizations in AL glomeruli, which could result in increased activity from a subset of the PNs (Hourcade et al, 2009). Even so, the observed changes would be widely distributed in the lip volume as the boutons of individual PNs are themselves widely scattered across the lip volume (Müller et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, plasticity of PN responses was observed both in Drosophila (Yu et al, 2004) and Apis (Fernandez et al, 2009). Supporting this view, LTM formation induces structural reorganizations in AL glomeruli, which could result in increased activity from a subset of the PNs (Hourcade et al, 2009). Even so, the observed changes would be widely distributed in the lip volume as the boutons of individual PNs are themselves widely scattered across the lip volume (Müller et al, 2002).…”
Section: Discussionmentioning
confidence: 73%
“…As a third control, bees from the paired ActD group received the same conditioning procedure as in the paired group, but were injected with 1 l of 1.5 mM Actinomycin D (Sigma-Aldrich) using a precision syringe (Hamilton) into their thorax, 3 h after learning. We previously showed that these conditions allowed to abolish LTM (Hourcade et al, 2009). To control for possible effects of the injection on memory, bees from all the other groups were injected with 1 l of PBS following the same procedure.…”
Section: Methodsmentioning
confidence: 99%
“…In the bee, a convergence between odor and sucrose pathways also exists at the level of the AL and the LH because VUMmx1, the instructive neuron that signals the presence of sucrose reward in the bee brain, contacts the olfactory circuit at these stages besides that of the MBs (50). Functional and structural changes have been found in the ALs of adult bees after elemental olfactory learning in the laboratory (66)(67)(68) or shortly after emergence in the hive (69,70). We thus suggest that, in the absence of functional MBs, elemental learning is still possible via the ALs.…”
Section: Discussionmentioning
confidence: 99%
“…The antennal lobes (ALs), primary olfactory centers receiving olfactory information from olfactory receptor neurons on the antennae, and the mushroom bodies (MBs), multimodal structures receiving processed olfactory information from the ALs as well as visual, mechanosensory, and gustatory input, are the main candidates for hosting long-term memory traces. Both regions exhibit structural modifications after formation of an olfactory l-LTM (Hourcade et al 2009(Hourcade et al , 2010Arenas et al 2012).…”
Section: Molecular Actors and Brain Regions In The Honeybeementioning
confidence: 99%